Industrial solid waste-based glue-solid powder additive for gold mining and preparation method thereof
By adding industrial solid waste and specific additives to the glue powder for gold mining, a stable network structure is formed, which solves the problem of insufficient strength and stability of glue powder, improves compressive strength and fluidity, and reduces the water secretion rate and linear shrinkage, suitable for high temperature environments in deep mine pits.
Patent Information
- Application Number
- CN202411504958.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing gold mining glue powder is insufficient after curing, has poor stability, is prone to cracking and settlement, and the reinforcement material is high and the construction difficulty increases, which affects the curing speed.
Using glue powder additives based on industrial solid waste, including waste molasses, sodium lignin sulfonate, triisopropanolamine, gluconic acid, ethylene glycol, surfactants, modified powders and enhancers, through modified poly Components such as carboxylic acid water reducer and vinyl silane oligomer Crosile® 1090 form a stable network structure, improve compressive strength and fluidity, and reduce water secretion and linear shrinkage.
The compressive strength, collapse degree, water discharge rate and linear shrinkage rate of glue powder are improved, especially at high temperatures, and the rational utilization of resources and the reduction of construction difficulty are achieved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of mine backfill materials, and in particular relates to a glue solid powder additive for gold mining based on industrial solid waste and a preparation method thereof. Background Art
[0002] In the process of non-ferrous metal and precious metal ore mining, backfill mining has been widely used, and the superiority of backfill technology has been increasingly recognized and accepted by people. Cement powder is a new type of cementitious material used to fill underground or mines. It is widely used in mine backfilling, underground grouting, road construction and other fields, with obvious economic and environmental benefits.
[0003] At present, the cement powder used in backfill mining in gold mines has the problem of insufficient strength after curing in actual applications, which may cause the backfill body to be unable to withstand the expected pressure. At the same time, the stability after curing is poor, which easily leads to problems such as cracking and sedimentation of the backfill body during use. In the prior art, reinforcing materials (such as fibers, chopped yarns, etc.) are added to the cement powder to improve the strength and stability of the cured body. However, the price of the reinforcing materials themselves is relatively high, especially high-performance fiber materials. After adding the reinforcing materials, the original construction process generally needs to be adjusted, which increases the construction difficulty and technical requirements. In addition, the reinforcing materials may affect the curing speed, and the proportion of the curing agent or the construction conditions need to be adjusted.
[0004] Therefore, there is an urgent need for a glue-solid powder additive for gold mining based on industrial solid waste and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a glue-solid powder additive for gold mining based on industrial solid waste and a preparation method thereof.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] The gold mining glue powder additive based on industrial solid waste includes the following raw materials in parts by weight: 12-16 parts of waste molasses, 2-6 parts of sodium lignin sulfonate, 10-14 parts of triisopropanolamine, 7-11 parts of gluconic acid, 1-5 parts of ethylene glycol, 2-6 parts of surfactant, 5-9 parts of modified powder, 5-10 parts of enhancer and 30-35 parts of water;
[0008] The enhancer comprises the following components in parts by mass: 1-3 parts of diethanol monoisopropanolamine, 11-14 parts of modified polycarboxylic acid water reducer, 3-6 parts of organosilicon defoamer and 4-7 parts of xylitol.
[0009] Furthermore, the preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:
[0010] (1) Mix 8-12 parts by mass of methyl allyl alcohol polyoxyethylene ether with 14-16 parts by mass of water, stir at 30-35° C. for 1-2 hours, and then add the mixture into a reaction kettle;
[0011] (2) 0.3-0.5 parts by weight of ammonium persulfate, 30-35 parts by weight of mixed monomers and 40-45 parts by weight of water are mixed and added dropwise to the reaction kettle of step (1) for 3-4 hours; then 0.16-0.19 parts by weight of 3-mercaptopropionic acid and 3-5 parts by weight of deionized water are mixed and added dropwise to the reaction kettle for 3-4 hours; finally 1.8-2.2 parts by weight of vinyl silane oligomer are added dropwise for 3-4 hours; after the addition is completed, the mixture is kept at 40-45° C. for 2-3 hours;
[0012] (3) After the heat preservation is completed, the mixture is cooled to room temperature and the pH is adjusted to neutral with a 35-40% by mass sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water reducer.
[0013] Furthermore, the mixed monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a mass ratio of 1: (1.4-1.6): (0.2-0.4).
[0014] Furthermore, the vinyl silane oligomer is a vinyl silane oligomer Crosile ® 1090.
[0015] The compressive strength of cement powder is directly related to the stability and safety of mine filling. The additive prepared by adding a reinforcing agent to the additive can improve the compressive strength of cement powder. The components in the reinforcing agent of the present invention can improve the dispersibility of cement powder. By introducing a vinyl silane oligomer containing organic functional groups of vinyl, propyl and ethoxy into the polycarboxylate water reducer, the compressive strength of cement powder can be improved. ® 1090 as a silane coupling agent, Crosile ® The silicon-methoxy functional groups generated after the hydrolysis of 1090 can enhance the interface bonding force between the components in the cement powder, help to form a continuous and stable network structure, and thus improve the compressive strength of the material. The reinforcing agent of the present invention also improves the fluidity of the cement powder and improves the slump.
[0016] Furthermore, the surfactant is selected from one or more of isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and isomeric tridecanol polyoxyethylene ether.
[0017] Furthermore, the surfactant comprises isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate and isomeric tridecanol polyoxyethylene ether in a mass ratio of (1.3-1.5):1:(0.4-0.7).
[0018] Bleeding refers to the phenomenon that water separates out of the slurry when it is static or vibrated. Too high a bleeding rate will cause the slurry to be unstable. The additive prepared by the present invention can reduce the bleeding rate of the cement powder by adding a surfactant to the additive. Analysis shows that the surfactant can make the components in the cement powder system more dispersible, and at the same time produce a synergistic effect with the water reducer, thereby achieving a balance between the appropriate dispersion effect and the control of bleeding. However, under this condition, the effect of the additive on improving the linear shrinkage of the cement powder is not ideal.
[0019] Furthermore, the preparation method of the modified powder comprises the following steps:
[0020] (1) Mixing montmorillonite, kaolin and silicon dioxide to obtain a mixed powder;
[0021] (2) Mix the mixed powder, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and ethanol in a mass ratio of 1:(5-7):(10-12), and ultrasonically react at 70-75°C for 6-8h, then filter, wash and dry to obtain a modified powder.
[0022] Furthermore, the mass ratio of montmorillonite, kaolin and silicon dioxide is (0.4-0.7):(1.3-1.6):(0.2-0.5).
[0023] Furthermore, the average particle size of montmorillonite is 17 μm, with a particle size range of 10-30 μm; the average particle size of kaolin is 1200 mesh, with a particle size range of 1000-1500 mesh; and the average particle size of silicon dioxide is 350 nm, with a particle size range of 200-500 nm.
[0024] The linear shrinkage of cement powder directly affects whether the backfill ore body will crack, which has an important impact on safety. The present invention attempts to add mixed powder to improve the improvement of the linear shrinkage by additives, but the effect is not ideal. The present invention obtains modified powder by modifying the mixed powder with 2-[2-(2-methoxyethoxy)ethoxy]acetic acid, and the prepared additive can reduce the linear shrinkage of cement powder. Analysis shows that 2-[2-(2-methoxyethoxy)ethoxy]acetic acid reacts with the hydroxyl groups on the surface of the mixed powder. The modified mixed powder is not easy to aggregate, which can improve the compatibility of the mixed powder with other components in the cement powder system, enhance the bonding force between the powder particles and the matrix of the cement powder, and reduce the shrinkage caused by poor bonding between the particles of the cement powder.
[0025] The temperature in deep mines is usually higher because the geothermal gradient causes the temperature to rise with increasing depth. For example, some gold mines in South Africa can reach a depth of more than 3 kilometers, and the temperature in the mine can reach more than 40°C. The compressive strength of the cementing agents currently on the market at high temperatures is not ideal. The present invention simultaneously uses a modified powder and a modified polycarboxylic acid water-reducing agent prepared from a mixed powder with a specific ratio, and the prepared additive can improve the compressive strength of the cementing powder at high temperatures. Analysis shows that under this condition, the modified powder and the modified polycarboxylic acid water-reducing agent can be simultaneously adsorbed on the surface of inorganic materials such as cement particles of the cementing agent, and work synergistically to form an adsorption film. This adsorption film can shield the attraction between the particles, prevent fine particles from reaggregating, and form a denser and more uniform structure, thereby improving the compressive strength of the cementing powder at high temperatures.
[0026] The invention provides a method for preparing a glue-solid powder additive for gold mining based on industrial solid waste, comprising the following steps: uniformly mixing waste molasses, sodium lignin sulfonate, triisopropanolamine, gluconic acid, ethylene glycol, a surfactant, a modified powder, a reinforcing agent and water to obtain the glue-solid powder additive for gold mining based on industrial solid waste.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. The present invention uses waste molasses from the sugar industry as raw material. The addition of waste molasses helps to improve the compressive strength of the cement powder, so that industrial solid waste resources are reasonably utilized. The cement powder additive prepared by the present invention can improve the slump, water bleeding rate, 28d uniaxial compressive strength, and linear shrinkage of the cement powder for gold mining, and at the same time improve the compressive strength effect of the cement powder at high temperature, and has extremely high market value.
[0029] 2. The present invention adds a reinforcing agent to the additive, and the additive prepared can improve the compressive strength of the cement powder.
[0030] 3. The present invention can reduce the water seepage rate of the cement powder by adding a surfactant to the additive.
[0031] 4. The present invention uses 2-[2-(2-methoxyethoxy)ethoxy]acetic acid to modify the mixed powder, and the prepared additive can reduce the linear shrinkage of the cement powder.
[0032] 5. The present invention uses modified powder prepared by using powders of specific proportions and modified polycarboxylic acid water-reducing agent at the same time, and the prepared additive can improve the compressive strength of the cement powder at high temperature. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The raw materials of the present invention are purchased from the following manufacturers:
[0035] Waste molasses is a by-product of industrial sugar production, including the following components: 35wt% sucrose, 8wt% glucose, 17wt% fructose, 1000mg / L dextran, and 2.2wt% total nitrogen.
[0036] Silicone defoamer, Evonik TegoFoamex842.
[0037] Methyl allyl alcohol polyoxyethylene ether was purchased from Suzhou Senfeida Chemical Co., Ltd., model HPEG-2400.
[0038] Vinyl silane oligomer Crosile ® 1090, purchased from Yongxiu County Aikopu New Materials Co., Ltd.
[0039] Isoprenoic acid polyoxyethylene ether was purchased from Hubei Dali Chemical Co., Ltd., TPEG-2400.
[0040] Isotridecyl alcohol polyoxyethylene ether, CAS: 9043-30-5.
[0041] 2-[2-(2-Methoxyethoxy)ethoxy]acetic acid, CAS: 16024-58-1.
[0042] The average particle size of montmorillonite was 17 μm, with a particle size range of 10-30 μm, and it was purchased from Zhejiang Fenghong New Materials Co., Ltd.
[0043] The average particle size of kaolin was 1200 mesh, the particle size range was 1000-1500 mesh, and it was purchased from Shijiazhuang Chenxing Industrial Co., Ltd.
[0044] The average particle size of silicon dioxide was 350 nm, with a particle size range of 200–500 nm, and it was purchased from Beijing Dekedaojin Technology Co., Ltd.
[0045] Example 1
[0046] The present embodiment provides a glue solid powder additive for gold mining based on industrial solid waste, including the following raw materials in parts by weight: 14 parts of waste molasses, 5 parts of sodium lignin sulfonate, 12 parts of triisopropanolamine, 9 parts of gluconic acid, 3 parts of ethylene glycol, 4 parts of surfactant, 7 parts of modified powder, 8 parts of enhancer and 32 parts of water.
[0047] The surfactant comprises isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate and isomeric tridecanol polyoxyethylene ether in a mass ratio of 1.4:1:0.6.
[0048] The enhancer comprises the following components in parts by mass: 2 parts of diethanol monoisopropanolamine, 12 parts of modified polycarboxylic acid water reducer, 5 parts of organosilicon defoamer and 6 parts of xylitol;
[0049] The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:
[0050] (1) Mix 9 parts by mass of methyl allyl alcohol polyoxyethylene ether with 15 parts by mass of water, stir at 32°C for 1.5 hours, and then add the mixture into a reactor;
[0051] (2) The mixed monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a mass ratio of 1:1.5:0.3; 0.4 parts by mass of ammonium persulfate, 32 parts by mass of the mixed monomer and 43 parts by mass of water are mixed and added dropwise to the reactor of step (1) for 3.5 hours; then 0.18 parts by mass of 3-mercaptopropionic acid and 4 parts by mass of deionized water are mixed and continued to be added dropwise to the reactor for 3.6 hours; finally, 2 parts by mass of vinyl silane oligomer Crosile ® 1090, the addition time is 3.4h; after the addition is completed, keep warm at 42℃ for 2.6h;
[0052] (3) After the heat preservation is completed, the mixture is cooled to room temperature and the pH is adjusted to neutral with a 38% by mass sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water reducer.
[0053] The preparation method of the modified powder comprises the following steps:
[0054] (1) Mixing montmorillonite, kaolin and silicon dioxide in a mass ratio of 0.6:1.5:0.4 to obtain a mixed powder; the average particle size of the montmorillonite is 17 μm, and the particle size range is 10-30 μm; the average particle size of the kaolin is 1200 mesh, and the particle size range is 1000-1500 mesh; the average particle size of the silicon dioxide is 350 nm, and the particle size range is 200-500 nm.
[0055] (2) Mix the mixed powder, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and ethanol in a mass ratio of 1:6:11, and ultrasonically react at 72° C. for 7 h, then filter, wash and dry to obtain a modified powder.
[0056] The preparation method of the glue-solid powder additive for gold mining based on industrial solid waste comprises the following steps: waste molasses, sodium lignin sulfonate, triisopropanolamine, gluconic acid, ethylene glycol, a surfactant, a modified powder, a reinforcing agent and water are uniformly mixed to obtain the glue-solid powder additive for gold mining based on industrial solid waste.
[0057] Example 2
[0058] This embodiment provides a gold mining glue powder additive based on industrial solid waste, including the following raw materials by weight: 12 parts of waste molasses, 2 parts of sodium lignin sulfonate, 10 parts of triisopropanolamine, 7 parts of gluconic acid, 1 part of ethylene glycol, 2 parts of surfactant, 5 parts of modified powder, 5 parts of enhancer and 30 parts of water. The surfactant includes isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate and isotridecyl alcohol polyoxyethylene ether in a mass ratio of 1.3:1:0.4.
[0059] The enhancer comprises the following components in parts by mass: 1 part of diethanol monoisopropanolamine, 11 parts of modified polycarboxylic acid water reducer, 3 parts of organosilicon defoamer and 4 parts of xylitol;
[0060] The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:
[0061] (1) Mix 8 parts by mass of methyl allyl alcohol polyoxyethylene ether with 14 parts by mass of water, stir at 30°C for 1 hour, and then add the mixture into a reactor;
[0062] (2) The mixed monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a mass ratio of 1:1.4:0.2; 0.3 parts by mass of ammonium persulfate, 30 parts by mass of the mixed monomer and 40 parts by mass of water are mixed and then added dropwise to the reactor of step (1) for 3 hours; then 0.16 parts by mass of 3-mercaptopropionic acid and 3 parts by mass of deionized water are mixed and then added dropwise to the reactor for 3 hours; finally 1.8 parts by mass of vinyl silane oligomer Crosile ® 1090, the addition time is 3h; after the addition is completed, keep warm at 40℃ for 2h;
[0063] (3) After the heat preservation is completed, the mixture is cooled to room temperature and the pH is adjusted to neutral with a 35% by mass sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water reducer.
[0064] The preparation method of the modified powder comprises the following steps:
[0065] (1) Mixing montmorillonite, kaolin and silicon dioxide in a mass ratio of 0.4:1.3:0.2 to obtain a mixed powder; the average particle size of the montmorillonite is 17 μm, and the particle size range is 10-30 μm; the average particle size of the kaolin is 1200 mesh, and the particle size range is 1000-1500 mesh; the average particle size of the silicon dioxide is 350 nm, and the particle size range is 200-500 nm.
[0066] (2) Mix the mixed powder, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and ethanol in a mass ratio of 1:5:10, and ultrasonically react at 70°C for 6 hours, and then filter, wash and dry to obtain a modified powder.
[0067] The preparation method of the glue-solid powder additive for gold mining based on industrial solid waste comprises the following steps: waste molasses, sodium lignin sulfonate, triisopropanolamine, gluconic acid, ethylene glycol, a surfactant, a modified powder, a reinforcing agent and water are uniformly mixed to obtain the glue-solid powder additive for gold mining based on industrial solid waste.
[0068] Example 3
[0069] This embodiment provides a gold mining glue powder additive based on industrial solid waste, including the following raw materials by weight: 16 parts of waste molasses, 6 parts of sodium lignin sulfonate, 14 parts of triisopropanolamine, 11 parts of gluconic acid, 5 parts of ethylene glycol, 6 parts of surfactant, 9 parts of modified powder, 10 parts of enhancer and 35 parts of water. The surfactant includes isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate and isomeric tridecanol polyoxyethylene ether in a mass ratio of 1.5:1:0.7.
[0070] The enhancer comprises the following components in parts by mass: 3 parts of diethanol monoisopropanolamine, 14 parts of modified polycarboxylic acid water reducer, 6 parts of organosilicon defoamer and 7 parts of xylitol;
[0071] The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps:
[0072] (1) Mix 12 parts by mass of methyl allyl alcohol polyoxyethylene ether and 16 parts by mass of water, stir at 35°C for 2 hours, and then add the mixture into a reactor;
[0073] (2) The mixed monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a mass ratio of 1:1.6:0.4; 0.5 parts by mass of ammonium persulfate, 35 parts by mass of the mixed monomer and 45 parts by mass of water are mixed and then added dropwise to the reactor of step (1) for 4 hours; then 0.19 parts by mass of 3-mercaptopropionic acid and 5 parts by mass of deionized water are mixed and then added dropwise to the reactor for 4 hours; finally, 2.2 parts by mass of vinyl silane oligomer Crosile ® 1090, the addition time is 4h; after the addition is completed, keep warm at 45℃ for 3h;
[0074] (3) After the insulation is completed, the mixture is cooled to room temperature and the pH is adjusted to neutral with a 40% by mass sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water reducer.
[0075] The preparation method of the modified powder comprises the following steps:
[0076] (1) Mixing montmorillonite, kaolin and silicon dioxide in a mass ratio of 0.7:1.6:0.5 to obtain a mixed powder; the average particle size of the montmorillonite is 17 μm, and the particle size range is 10-30 μm; the average particle size of the kaolin is 1200 mesh, and the particle size range is 1000-1500 mesh; the average particle size of the silicon dioxide is 350 nm, and the particle size range is 200-500 nm.
[0077] (2) Mix the mixed powder, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and ethanol in a mass ratio of 1:7:12, and ultrasonically react at 75°C for 8 hours, and then filter, wash and dry to obtain a modified powder.
[0078] The preparation method of the glue-solid powder additive for gold mining based on industrial solid waste comprises the following steps: waste molasses, sodium lignin sulfonate, triisopropanolamine, gluconic acid, ethylene glycol, a surfactant, a modified powder, a reinforcing agent and water are uniformly mixed to obtain the glue-solid powder additive for gold mining based on industrial solid waste.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is: 6 parts of surfactant, 1 part of modified powder, and 12 parts of reinforcing agent.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that the enhancer comprises the following components in parts by mass: 6 parts of diethanol monoisopropanolamine, 9 parts of modified polycarboxylic acid water reducer, 8 parts of organosilicon defoamer and 2 parts of xylitol.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 1 is that the vinyl silane oligomer Crosile® 1090 is replaced by the silane coupling agent KH560.
[0085] Comparative Example 4
[0086] The difference between this comparative example and Example 1 is that montmorillonite, kaolin and silicon dioxide are mixed in a mass ratio of 1:1:1 to obtain a mixed powder.
[0087] Comparative Example 5
[0088] The difference between this comparative example and Example 1 is that the average particle size of montmorillonite is 35 μm, and the particle size range is 20-50 μm (purchased from Zhejiang Fenghong New Materials Co., Ltd.); the average particle size of kaolin is 2000 mesh, and the particle size range is 1400-2500 mesh (purchased from Shijiazhuang Chenxing Industrial Co., Ltd.); the average particle size of silicon dioxide is 500 nm, and the particle size range is 400-700 nm. (Purchased from Beijing Dekedaojin Technology Co., Ltd.).
[0089] Comparative Example 6
[0090] The difference between this comparative example and Example 1 is that the surfactant comprises isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate and isomeric tridecyl alcohol polyoxyethylene ether in a mass ratio of 1:1:1.
[0091] Comparative Example 7
[0092] The difference between this comparative example and Example 1 is that the surfactant includes Tween-60, sodium fatty acid and dodecylamine polyoxyethylene ether (purchased from Hai'an Petrochemical Plant, Jiangsu Province) in a mass ratio of 1.4:1:0.6.
[0093] Performance Testing
[0094] The adhesive powder is prepared using the additives of Examples 1-3 and Comparative Examples 1-7. The specific method is as follows: by mass, 10 parts of Portland cement clinker, 10 parts of coal gangue, 25 parts of fly ash, 3 parts of desulfurized gypsum, 2 parts of slag and 1.5 parts of additives are mixed and mixed evenly in a mixer to obtain adhesive powder.
[0095] With reference to GB / T39489-2020, the slump, water seepage rate, 28d uniaxial compressive strength and linear shrinkage of the above-mentioned cement powder were measured. The 28d uniaxial compressive strength was measured after curing at 25°C and 50% humidity for 28 days and at 45°C and 50% humidity for 28 days.
[0096] Table 1 Performance test results
[0097]
[0098] It can be seen from the above performance test results that the additives of Examples 1-3 can improve the performance of the cement powder for gold mining, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic compounding of multiple components of the additives.
[0099] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the ratio of the surfactant, the modified powder and the reinforcing agent is changed, and it can be seen that the comprehensive effect of the glue powder is reduced, proving that these three components have a synergistic effect on the performance of the additive. In comparative example 2, the formula of the components in the reinforcing agent is changed, which affects the compressive strength and slump of the glue powder. In comparative example 3, the preparation method of the modified polycarboxylic acid water reducer is changed. From the results, it can be seen that the compressive strength of the glue powder at room temperature and high temperature is reduced; the raw material ratio and powder parameters used in the modified powders of comparative examples 4 and 5 are changed, which affects the linear shrinkage of the glue powder and also affects the compressive strength of the glue powder at high temperature. The ratio and composition of the surfactants in comparative examples 6-7 are changed, which affects the water seepage rate of the glue powder. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0100] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A gold mining glue powder additive based on industrial solid waste, characterized in that: The invention comprises the following raw materials in parts by weight: 12-16 parts of waste molasses, 2-6 parts of sodium lignin sulfonate, 10-14 parts of triisopropanolamine, 7-11 parts of gluconic acid, 1-5 parts of ethylene glycol, 2-6 parts of surfactant, 5-9 parts of modified powder, 5-10 parts of enhancer and 30-35 parts of water; The enhancer comprises the following components in parts by mass: 1-3 parts of diethanol monoisopropanolamine, 11-14 parts of modified polycarboxylic acid water reducer, 3-6 parts of organosilicon defoamer and 4-7 parts of xylitol; The preparation method of the modified polycarboxylate water-reducing agent comprises the following steps: (1) Mix 8-12 parts by mass of methyl allyl alcohol polyoxyethylene ether with 14-16 parts by mass of water, stir at 30-35°C for 1-2 hours, and then add the mixture into a reaction kettle; (2) 0.3-0.5 parts by weight of ammonium persulfate, 30-35 parts by weight of mixed monomers and 40-45 parts by weight of water are mixed and added dropwise to the reaction kettle of step (1) for 3-4 hours; then 0.16-0.19 parts by weight of 3-mercaptopropionic acid and 3-5 parts by weight of deionized water are mixed and added dropwise to the reaction kettle for 3-4 hours; finally 1.8-2.2 parts by weight of vinyl silane oligomer are added dropwise for 3-4 hours; after the addition is completed, the mixture is kept at 40-45° C. for 2-3 hours; (3) After the heat preservation is completed, the mixture is cooled to room temperature, and the pH is adjusted to neutral with a 35-40% by mass sodium hydroxide aqueous solution to obtain a modified polycarboxylic acid water reducer; The mixed monomer is a mixture of methacrylic acid, acrylic acid and maleic anhydride in a mass ratio of 1: (1.4-1.6): (0.2-0.4); Vinyl silane oligomer is vinyl silane oligomer Crosile ® 1090; The surfactant comprises isopentanol polyoxyethylene ether, sodium dodecylbenzene sulfonate and isomeric tridecanol polyoxyethylene ether in a mass ratio of (1.3-1.5):1:(0.4-0.7); The preparation method of the modified powder comprises the following steps: (1) Mixing montmorillonite, kaolin and silicon dioxide to obtain a mixed powder; (2) Mixing a mixed powder, 2-[2-(2-methoxyethoxy)ethoxy]acetic acid and ethanol in a mass ratio of 1:(5-7):(10-12), ultrasonically reacting at 70-75° C. for 6-8 hours, and then filtering, washing and drying to obtain a modified powder; The mass ratio of montmorillonite, kaolin and silica is (0.4-0.7): (1.3-1.6): (0.2-0.5); The average particle size of montmorillonite is 17 μm, and the particle size range is 10-30 μm; the average particle size of kaolin is 1200 mesh, and the particle size range is 1000-1500 mesh; the average particle size of silicon dioxide is 350 nm, and the particle size range is 200-500 nm.
2. A method for preparing a glue-solid powder additive for gold mining based on industrial solid waste according to claim 1, characterized in that: The following steps are involved: The waste molasses, sodium lignin sulfonate, triisopropanolamine, gluconic acid, ethylene glycol, a surfactant, a modified powder, a reinforcing agent and water are uniformly mixed to obtain a glue solid powder additive for gold mining based on industrial solid waste.